Revealing differences in flavor compounds during plum wine fermentation using single and mixed yeast strains through metabolomic analysis - Tian Li; Mengsheng Deng; Shuang Li; Yu Lei; Dong Li; Ke Li (Food Chemistry: X, 2025)
Mixed fermentation can enhance the flavor and aroma of fruit wine, but the mechanisms driving this enhancement remain unclear. This study used non-targeted metabolomics to analyze the effects of mixed versus single fermentation on plum wine flavor. The results showed that compared with single fermentation, mixed fermentation reduced ethanol content and the ability to consume reducing sugars. In single fermentation, volatile compounds increased over time, while in mixed fermentation, they first increased and then declined. Mixed fermentation notably increased esters and reduced higher alcohols, with key differentiators including phenethyl acetate, hexyl acetate, isoamyl acetate, ethyl acetate, isoamyl alcohol, phenethyl alcohol, ethyl caproate, and isobutanol. Furthermore, 40 differential non-volatile flavor compounds were identified, with amino acids emerging as the predominant differentiators. The annotation analysis of these compounds revealed 11 important metabolic pathways for proline, aspartate, glutamate, and β-alanine metabolism. These findings provide insight about producing plum wines with distinct flavor profiles.